Sikap dan Persepsi Konsumen Terhadap Minat Menggunakan Kereta Api Jarak Jauh pada Masa Pandemi Covid 19 - Aisyah Rahmawati (Institut Transportasi dan Logistik Trisakti, 2020)
This study aims to determine the extent to which consumer attitudes and perceptions of the interest or desire of the public to use the train as the preferred means of transportation during the Covid 19 pandemic, either partially or simultaneously. In this study using quantitative methods with multiple regression analysis, t-test, and f test to determine the effect of variables either partially or simultaneously using a convenience sample of 96 respondents. The results show that there is a positive and significant influence both partially and simultaneously on consumer attitudes and perceptions of interest in using trains during the Covid 19 pandemic.